Cahaya Kemuliaan: Minyak Zaitun Sebagai Simbol Kehadiran Ilahi dalam Kemah Suci (IMAMAT 24:1-4) - Veronika Tumangger; Landong Sihombing (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
Leviticus 24:1-4 outlines the procedures for administering the holy oil and bread in the Temple as part of the required worship. This article highlights the importance of purity and proper offerings in the worship of God. Through theological analysis, this journal explains the depth of the symbolic meaning of the holy oil and bread, as well as their relevance in understanding the role of service and worship in ancient Jewish religious traditions